Postacute care outcomes and medicare payments for patients treated by physicians and advanced practitioners who specialize in nursing home practice. (20th March 2019) - Ryskina, Kira L.; Yuan, Yihao; Werner, Rachel M.
Abstract : Objective: To measure the association between clinician specialization in nursing home (NH) practice and outcomes of patients who received postacute care in skilled nursing facilities (SNFs). Data Sources: Medicare claims and NH assessments for 2 118 941 hospital discharges to 14 526 SNFs in January 2012‐October 2014 and MD‐PPAS data for 52 379 clinicians. Study Design: Generalist physicians and advanced practitioners with ≥ 90 percent of claims for NH‐based care were considered NH specialists. The primary clinician during each SNF stay was determined based on plurality of claims during that stay. We estimated the effect of being treated by a NH specialist on 30‐day rehospitalizations, successful discharge to community, and 60‐day episode‐of‐care Medicare payments (Parts A and B). All models included patient demographics, clinical variables, and SNF fixed effects. Principal Findings: Nursing home specialists' patients were less likely to be rehospitalized (14.71 percent vs 16.23 percent; adjusted difference, −1.51 percent, 95% CI −1.78 to −1.24), more likely to be successfully discharged to community (56.33 percent vs 55.49 percent; adjusted difference, 0.84 percent, 95% CI 0.54 to 1.14), but had higher 60‐day Medicare payments (31 628 vs 31 292; adjusted difference, 335; 95% CI 242 to 429). Conclusions: Clinicians who specialize in NH practice may achieve better postacute care outcomes at slightly higher costs.